2021
DOI: 10.1103/physrevfluids.6.033904
|View full text |Cite
|
Sign up to set email alerts
|

Control of droplet evaporation on smooth chemical patterns

Abstract: We investigate the evaporation of a two-dimensional droplet on a solid surface. The solid is flat but with smooth chemical variations that lead to a space-dependent local contact angle. We perform a detailed bifurcation analysis of the equilibrium properties of the droplet as its size is changed, observing the emergence of a hierarchy of bifurcations that strongly depends on the particular underlying chemical pattern. Symmetric and periodic patterns lead to a sequence of pitchfork and saddle-node bifurcations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…As the droplet slowly evaporates the shape and location of the droplet can be modelled by studying the stability of the equilibrium solutions. This approach has recently been used to describe droplets evaporating on chemical patterns [39] and droplet with mass transfer moving on chemical patterns [40]. This section reviews the work presented in these references to study the static stability of a droplet with known volume on a smooth patterned surface.…”
Section: Stability Analysis: Bifurcation Diagramsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the droplet slowly evaporates the shape and location of the droplet can be modelled by studying the stability of the equilibrium solutions. This approach has recently been used to describe droplets evaporating on chemical patterns [39] and droplet with mass transfer moving on chemical patterns [40]. This section reviews the work presented in these references to study the static stability of a droplet with known volume on a smooth patterned surface.…”
Section: Stability Analysis: Bifurcation Diagramsmentioning
confidence: 99%
“…2w) is a integer multiple of the pattern wavelength. It has been shown that only the droplets which align with a maximum or minimum of the patterning can be stable [39,40]. In addition, the stability of those solutions depend on the droplet's volume and solutions that are centred on a maximum or minimum of the patterning can be stable, partially stable (saddle node) or fully unstable.…”
Section: Stability Analysis: Bifurcation Diagramsmentioning
confidence: 99%
See 3 more Smart Citations